Numerical studies of magnon bound states in the planar antiferromagnet α-NaMnO2 - Heng, Alvin Jun Ren (Nanyang Technological University, 2020)
Recent neutron scattering experiments on the planar antiferromagnet a-NaMnO2 have revealed unusual spin dynamics in the Mn3+ plane, which are effective S = 2 moments. Conventionally, one does not expect S = 2 systems to host strongly quantum excitations. However, inelastic neutron scattering experiments on the compound have revealed the existence of two and three magnon bound state ex- citations, with a measurable binding energies between the magnons. In particular, the two magnon bound state was found to be longitudinally-polarized, which comes in contrast to transverse spin waves that are more commonly studied in magnetic systems. Motivated by these discoveries, in this project we study a S = 2 Heisenberg antiferromagnet with easy-axis anisotropy, using numerically exact simulations based on Matrix Product State techniques. We find from the calculated spectral functions the existence of a sharp single magnon peak, followed by signatures of two and three magnon bound states, strongly supporting the experimental findings. We then proceed to fit the numerical data to experimental data to obtain estimations of the Hamiltonian parameters for the system.